Exploring the impact of light wavelength on indoor mould growth - Izmir Tunahan, Gizem; Hetherington, Ella; Barrett, Edward; Altamirano, Hector (Frontiers in Built Environment, 2025)
Mould growth adversely impacts the structural integrity of buildings, human health and indoor air quality. Traditional mould prevention in buildings primarily focuses on humidity control and ventilation, while the potential of lighting as a non-chemical strategy remains underexplored. This research examines how various lighting configurations affect the growth dynamics of two common indoor mould species found in UK dwellings. In this study, cultures were incubated under continuous illumination with either long-wavelength (650–700 nm) or short-wavelength (435–465 nm) LED light alongside dark conditions at two water activity levels (aw 0.95 and aw 0.91). Mycelial growth was quantified by measuring colony diameter and dry cell weight, and spore concentration was measured using a hemacytometer. Results showed that for Aspergillus Niger, long-wavelength light significantly increased both mycelial growth and conidia production in both high and low-water activities. Short-wavelength light irradiation resulted in the lowest conidia production, suggesting that short wavelengths could inhibit spore formation. For Cladosporium sphaerospermum, long wavelength light also increased conidia production; however, it only resulted in higher mycelial growth in higher water activity media. This study shows that incorporating spectrally optimised lighting systems into building designs could generate mould-resistant conditions and minimise the need for chemical treatments while enhancing indoor air quality. Further research is recommended to investigate broad-spectrum lighting with a wide range of wavelengths on mould growth to determine the most effective spectral conditions for mould prevention in the built environment.